Weaving the Web - Berners-Lee, Tim. (Orion Business, 1999)
Enquire within upon everything. Tangles, links and webs. Info.cern.ch. Protocols. Going global. Browsing. Changes. Consortium. Competition and consensus. Web of people. Privacy. Mind to mind. Machines and the web. Weaving the web